2018
DOI: 10.1001/jamasurg.2017.4477
|View full text |Cite
|
Sign up to set email alerts
|

Risks Associated With Primary and Redo Carotid Endarterectomy in the Endovascular Era

Abstract: IMPORTANCE Clinical experience suggests worse outcomes for redo carotid endarterectomy (CEA) relative to primary CEA. Objective quantification of the excess risk attributable to redo CEA in this era of proliferating endovascular therapy remains to be determined. OBJECTIVE To evaluate the risks of redo CEA relative to primary CEA. DESIGN, SETTING, AND PARTICIPANTSThis study was a retrospective analysis of a prospective cohort of patients maintained by the Society for Vascular Surgery in the Vascular Quality Ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This data goes in line with the proportion of asymptomatic patients undergoing carotid revascularization for carotid artery stenosis in the United States. [42][43][44] However, given the results obtained from this study and several previous studies, 25 there is a raised concern about performing redo-CEA in asymptomatic patients, especially with moderate restenosis, because the postoperative course of the procedure is not benign, arousing a conservative approach of watchful waiting by some physicians. However, O'Donnell et al 45 showed that nonoperative management in patients with high-grade (>75%) recurrent stenosis was associated with 7.5% stroke rate compared with 2.1% among patients managed operatively.…”
Section: Discussionmentioning
confidence: 86%
“…This data goes in line with the proportion of asymptomatic patients undergoing carotid revascularization for carotid artery stenosis in the United States. [42][43][44] However, given the results obtained from this study and several previous studies, 25 there is a raised concern about performing redo-CEA in asymptomatic patients, especially with moderate restenosis, because the postoperative course of the procedure is not benign, arousing a conservative approach of watchful waiting by some physicians. However, O'Donnell et al 45 showed that nonoperative management in patients with high-grade (>75%) recurrent stenosis was associated with 7.5% stroke rate compared with 2.1% among patients managed operatively.…”
Section: Discussionmentioning
confidence: 86%
“…Although this issue has been emphasized in carotid surgery, further studies are needed to prove this because the behavior of the vessels and complications may differ in different vascular sites/procedures. 22 The meticulous excessive dissection needed in the redo-AVF group may explain the longer operative time in this group. Our operative time in the remaining groups was comparative to what Kumar et al 23 reported in their series.…”
Section: Discussionmentioning
confidence: 96%
“…Although this issue has been emphasized in carotid surgery, further studies are needed to prove this because the behavior of the vessels and complications may differ in different vascular sites/procedures. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Outcomes in Asymptomatic Redo Carotid Endartectomy A Word of Caution Rishi A. Roy, MD; Gilbert R. Upchurch Jr, MD Arhuidese et al 1 compare primary carotid endartectomy (CEA) and redo CEA using the Society for Vascular Surgery Vascular Quality Initiative database. 1 This large study compares 64 118 primary CEAs with 1369 redo CEAs, with the primary outcomes of stroke, death, myocardial infarction, stroke/ death, and stroke/death/ myocardial infarction at 30 days and at 1-year follow-up. The higher incidence of stroke, death, stroke/death, and stroke/death/ myocardial infarction in the asymptomatic redo CEA group compared with the primary CEA group but not in the symptomatic patients is the primary finding in this study.…”
Section: Invited Commentarymentioning
confidence: 99%
“…Arhuidese et al compare primary carotid endartectomy (CEA) and redo CEA using the Society for Vascular Surgery Vascular Quality Initiative database . This large study compares 64 118 primary CEAs with 1369 redo CEAs, with the primary outcomes of stroke, death, myocardial infarction, stroke/death, and stroke/death/myocardial infarction at 30 days and at 1-year follow-up.…”
mentioning
confidence: 99%